Artemisinin analog SM934 alleviates epithelial barrier dysfunction via inhibiting apoptosis and caspase-1-mediated pyroptosis in experimental colitis - Shao, Meijuan; Yan, Yuxi; Zhu, Fenghua; Yang, Xiaoqian; Qi, Qing; Yang, Fangming; Hao, Tingting; Lin, Zemin; He, Peilan; Zhou, Yu; Tang, Wei; He, Shijun; et al. (Frontiers in Pharmacology, 2022)
Intestinal barrier disruption due to the intestinal epithelial cells’ (IECs) death is one of the critical pathological features of inflammatory bowel diseases (IBDs). SM934, an artemisinin analog, has previously been proven to ameliorate colitis induced by dextran sulfate sodium (DSS) in mice by suppressing inflammation response. In this study, we investigated the protective effects of SM934 on the epithelial barrier and the underlying mechanism in trinitrobenzene sulfonic acid (TNBS)-induced colitis mice. We demonstrated that SM934 restored the body weight and colon length, and improved the intestine pathology. Furthermore, SM934 treatment preserved the intestinal barrier function via decreasing the intestinal permeability, maintaining epithelial tight junction (TJ) protein expressions, and preventing apoptosis of epithelial cells, which were observed both in the colon tissue and the tumor necrosis factor-α (TNF-α)-induced human colonic epithelial cell line HT-29. Specifically, SM934 reduced the pyroptosis of IECs exposed to pathogenic signaling and inhibited pyroptosis-related factors such as NOD-like receptor family pyrin domain containing 3 (NLRP3), adapter apoptosis-associated speck-like protein (ASC), cysteine protease-1 (caspase-1), gasdermin (GSDMD), interleukin-18 (IL-18), and high-mobility group box 1 (HMGB1) both in colon tissue and lipopolysaccharide (LPS) and adenosine triphosphate (ATP) co-stimulated HT-29 cells in vitro. Moreover, SM934 interdicted pyroptosis via blocking the transduction of mitogen-activated protein kinase (MAPK) and nuclear factor-kB (NF-kB) signaling pathways. In conclusion, SM934 protected TNBS-induced colitis against intestinal barrier disruption by inhibiting the apoptosis and pyroptosis of epithelial cells via the NLRP3/NF-κB/MAPK signal axis, and intestinal barrier protection in company with an anti-inflammatory strategy might yield greater benefits in IBD treatment.